PREDICTIVE ROLE OF CONNEXIN 40 IN THE PATHOGENESIS OF HEREDITARY SICK SINUS SYNDROME - S. Yu. Nikulina; A. A. Chernova; V. A. Shulman; T. S. Kukushkina; M. I. Voevoda; V. N. Maksimov (Столичная издательская компания, 2016)
Aim. To study the association of hereditary sick sinus syndrome (SSS) with connexin 40 gene (Cx40) polymorphism. Material and methods. 29 families with hereditary SSS were involved into prospective study. Probands were 20 women and 9 men (aged 58±0.15). Relatives, I-III degree of kinship, were 65 men and 68 women (aged 39±0.13). Clinical and instrumental examination was performed in all probands and their relatives. Diagnosis of SSS was verified by transesophageal atrial electrostimulation. Molecular genetic investigation of SSS patients and their relatives was carried out in laboratory of medical genetics of Research Institute of Therapy , Siberian Branch of Russian Academy of Medical Sciences. Results. 71 SSS patients, 44 their healthy relatives, I-III degree of kinship, 197 subjects of control group were genotyped for the polymorphism of 44G>A of gene Cx40. According to allele-specific polymerase chain reaction 3 types of genotypes ADRA2B (II - homozygous wild, ID - heterozygous, DD - homozygous mutant) were found in SSS patients, their relatives and healthy subjects of control group. Conclusion. Significant predominance of the heterozygous genotype 44G>A was found in SSS (45,07±5,9%) patients in comparison with subjects of the control group (29,44±3,2%).